Remarks about the Historical Character of Ecological Anthropology - Kośmicki, Eugeniusz (Anthropological Review, 1987)
The description and explanation of the relation between man and his natural surrounding is the subject of ecological anthropology. The characteristic feature of this science is primarily the historical interpretation of the economic process of taking into possession and transforming the life environment, and also the ideological way of justifying the accepted adaptation strategy. One can distinguish hunting-gatherer agricultural, industrial and postindustrial methods of taking nature into possession. Definite ideological and consciousness dependent subsystems correspond to. these methods of taking nature into possession.In case of: hunting-gatherer societies the degree of influencing nature was comparatively small. A considerably wider degree of taking into possession and transforming life environment occurs in agricultural societies. Next to the achievements of culture already then there occurred strong processes of environmental devastation. In the period of the development of agricultural societies based on class unequality, higher religions were developed which insured to those societies the social and ecological stability. Starting with the 18th century the industrial activity becomes the basic way of taking nature into possession. Due to enormous exploitation of the natural resources there follows a speedy increase of population and its needs. The effect of these activities is the. development of the global ecological crisis. There appears the conception of anthropogenical homeostasis as the regulator of the process of taking nature into possession by postindustrial societies. It is accompanied by extensively developed ecological consciousness revealed among others in the form of economy and ecological ethics.